Dementia in the Oldest-Old: A Nationwide Inpatient Sample Database Analysis. (April 2016) - Sherzai, Dean; Sherzai, Ayesha; Babayan, Diana; Chiou, Daniel; Vega, Sonia; Shaheen, Magda
Objective: The aim of this study was to explore gender and race-specific mortality and comorbidities associated with dementia hospitalizations among the oldest-old.Method: Using the 1999-2008 Nationwide Inpatient Sample, we identified the association between dementia mortality and hospital characteristics in the oldest-old population.Results: The oldest-old population was mostly comprised of Whites (81.1%) and women (76.0%), had shorter length of hospital stay (6.12 days), and lower hospital charges (US$18, 770.32) than the young-old, despite the higher in-hospital mortality. Crude in-hospital mortality was higher for White males in the young-old population, followed by Hispanics and African Americans. However, Hispanic males had the highest mortality, followed by Whites then African Americans in the oldest-old group. After adjusting for different variables, these relationships did not change.Discussion: There should be a greater focus on potential pre-existing biases regarding hospital care in the elderly, especially the oldest-old and elderly minority groups.